If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -2n = 0 Solving 13 + -2n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -2n = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -2n = 0 + -13 -2n = 0 + -13 Combine like terms: 0 + -13 = -13 -2n = -13 Divide each side by '-2'. n = 6.5 Simplifying n = 6.5
| 3(x-4)=5-2(3x+5) | | 4(k-6)=6 | | -0.6(m+10)=-4 | | 18=0.80x | | 4x-7y=-6 | | 4x^2-13x+1=0 | | 7r+9=51 | | 4z-6=3z+12 | | 4.8x=2.4 | | -3w=2 | | -100=10x-30 | | -7x+9y=6 | | 3(1+-2x)=3-6x | | -19w=16 | | 8x^2+4x=-9 | | 15x^4*35x^2= | | 10z-10=9z+36 | | x-10.38=13.11 | | 5-(x+7)+4x=-7(x-1) | | log(6)(x+4)=3 | | 3/7(2p-14)6/7p-6 | | -35x+35x=-30+30 | | a^4-a^3-a=12 | | 15+x=19.36 | | a(x-3)=4x | | 11(-23)+29(-29)= | | Y+8=3y | | x^2-x-38=4x-2 | | 1.6(x-2.8)=(0.2x+1.5)-0.7 | | 7/2x-5/3x=22/3 | | f(0)=l(0)-6l | | 2(x-1)+3=x+3-(x-2) |